Efektivitas Latihan Yoga dalam Mengatasi Penyakit Jantung Koroner (PJK) - Kadek Dwitya Widi Adnyani; Made G Juniartha (Jurnal Yoga dan Kesehatan, 2020)
Lifestyle or unhealthy lifestyles lead to unhealthy body conditions. This disturbs everyday human life. Unhealthy body conditions cause various diseases, one of which is cardiovascular disease that attacks the heart organ. Coronary heart disease is a disease that attacks the coronary arteries, where the coronary arteries are narrowed due to an imbalance of oxygen and nutrients produced with the needs of the heart. This can have an unhealthy impact on the heart and can cause death. Yoga practice can be used as an effort to reduce coronary heart disease because yoga practice helps balance the oxygen demand and oxygen supply produced by the body, so that the imbalance can be overcome and the heart becomes healthier. The percentage of narrowing of the arteries will decrease as a result of chest pain or angina pectoris will not be felt and coronary heart disease can be overcome.